Substituted Diindenopyrazinediones with symmetrical Polyalkyl-carbazole for high-efficiency blueish green solution-processable OLED. (July 2017) - Zhang, Lei; Bai, Yongqi; Liu, Zhiyang; Jiang, Weigang; Lei, Tao; Yang, Rongjuan; Islam, Amjad; Zhang, Yumei; Ouyang, Xinhua; Ge, Ziyi
Abstract: Much effort has been devoted to design and synthesize this solution-processable OLEDs, Some significant advances have been achieved with the power efficiencies. However, most of them still lag behind those of evaporated non-doping OLEDs. Two novel peripheral Polyalkyl-carbazole substituted Diindeno-pyrazinediones have been developed for highly-efficient and solution-processable OLEDs. Provide high efficient materials for the solution-processed to reduce costs of OLEDs. By fine-tuning their carriers transfer and injection barriers, solution-processed device based on DTPADIPY-TCz shows highly efficient bluish green emission with a maximum power efficiency (PE) of 6.88 lm W −1, which is among the highest reported to date for solution-processable fluorescent OLEDs with a relatively low efficiency roll-off. Graphical abstract: Highlights: We have designed and synthesized two kinds of solution-processable Substituted Diindenopyrazinediones with improved carrier transport. Solution-processed device shows PEmax and CEmax of 2.20 l m W −1 and 2.49 cd A −1 . By fine-tuning their carries transfer and injection barriers, DTPADIPY-TCz shows a relatively low efficiency roll-off.